Aboriginal Knowledge Infusion in Initial Teacher Education at the Ontario Institute for Studies in Education at the University of Toronto - Mashford-Pringle, Angela; Nardozi, Angela G (International Indigenous Policy Journal, 2013)
Knowledge of the Aboriginal socio-political history in Canada has historically been excluded from public education. In Ontario, public school children learn about Aboriginal people at specific times in the curriculum. However, teachers frequently only teach the bare essentials about Aboriginal people in Canada because they do not have adequate knowledge or feel that they lack the ability to teach about this subject. The Ontario Institute of Studies in Education at the University of Toronto has implemented the Deepening Knowledge Project to provide teacher candidates with an increased awareness and knowledge about Aboriginal history, culture, and worldview for their future teaching careers. This article will provide insight into the project and the curriculum developed for working with teacher candidates.